PEMIKIRAN PENDIDIKAN ISLAM SYEKH NAWAWI AL-BANTANI DAN RELEVANSINYA TERHADAP PENDIDIKAN MORAL ERA KONTEMPORER - Muhammad Yusuf (Rabbani: Jurnal Pendidikan Agama Islam, 2022)
Islamic education must be able to assist humans in developing the basic potentials of Islamic humans, including the creation of noble character, ethics, and perfect morals. Morals must go through a certain treatment process if someone wants to have good morals. To develop good morals or Islamic morals itself, one of them can be pursued through educational activities or processes, especially Islamic education. This research uses library research. Data collection techniques using documentation techniques and data analysis techniques are descriptive analysis. Syekh Nawawi al-Bantani in education is very much oriented to religious values ​​and how to make God the target object in the educational process so that some researchers classify him as a Conservative Religious scholar. The concepts of educational thought, especially those related to moral education, are still very relevant to be applied in today's contemporary era.